2022
DOI: 10.1002/clc.23955
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values of coronary artery calcium and arterial stiffness for long‐term cardiovascular events in patients with stable coronary artery disease

Abstract: Background Subclinical atherosclerosis detected by increased coronary artery calcium (CAC) or arterial stiffness as reflected by cardio‐ankle vascular index (CAVI) has been associated with major adverse cardiovascular events (MACEs). However, comparative data from these two assessments in the same population are still limited. Methods From 2005 to 2013, patients with stable coronary artery disease (CAD), both asymptomatic and symptomatic who underwent both coronary computed tomography and CAVI were enrolled an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
0
0
Order By: Relevance
“…Multivariate regression analysis revealed that increasing age ≥ 55 years, Framingham risk score > 10, CACS ≥ 400, BMI ≥ 30, and proximal segment lesions were the independent predictors of clinical outcomes. In concordance with this nding, age ≥ 60 years, CACS ≥ 400, and BMI ≥ 23 were highly characteristic of MACE occurrence and increased mortality incidence in Limpijankit et al, [31] study on 8687 patients with chronic stable angina. Similarly, Jensen et al, [22] established the relationship between BMI, CACS, and cardiac outcomes by studying 36509 patients and found that patients with BMI ≥ 30 kg/m² had a higher prevalence of CACS ≥ 400 and were at a greater risk of IHD, CVD, and all-cause mortality in comparison with those with normal BMI.…”
Section: Discussionsupporting
confidence: 74%
“…Multivariate regression analysis revealed that increasing age ≥ 55 years, Framingham risk score > 10, CACS ≥ 400, BMI ≥ 30, and proximal segment lesions were the independent predictors of clinical outcomes. In concordance with this nding, age ≥ 60 years, CACS ≥ 400, and BMI ≥ 23 were highly characteristic of MACE occurrence and increased mortality incidence in Limpijankit et al, [31] study on 8687 patients with chronic stable angina. Similarly, Jensen et al, [22] established the relationship between BMI, CACS, and cardiac outcomes by studying 36509 patients and found that patients with BMI ≥ 30 kg/m² had a higher prevalence of CACS ≥ 400 and were at a greater risk of IHD, CVD, and all-cause mortality in comparison with those with normal BMI.…”
Section: Discussionsupporting
confidence: 74%
“…Although current diagnostic modalities for CAD mainly focus on ischemic lesions, plaque composition and morphology are developing as strong predictors for cardiac events even without confirmed ischemia ( 24 ). As shown in previous data, a higher burden of calcification in patients with stable CAD predicts long-term cardiovascular event occurrence ( 25 ). Accumulating evidence has revealed that vascular calcification is a complex biological process involving diverse pathophysiological mechanisms in which the phosphorous and calcium milieu and vascular smooth muscle cells play important roles, and vascular calcification is considered a vascular pathological disorder related to a variety of diseases ( 23 , 26 ).…”
Section: Discussionsupporting
confidence: 67%
“…Regarding the prognostic utility of CAVI in SLE patients, its employment for cardiovascular risk stratification could revolutionize patients' management by endorsing more aggressive therapeutic approaches in otherwise uncomplicated SLE patients. Numerous studies have demonstrated the association of CAVI with the development of cardiovascular events in patients with established atherosclerotic CVDs (ASCVDs) [33,34] or those at high risk for ASCVDs [35]. No data are available for the prognostic value of CAVI in the SLE population and this remains to be proved.…”
Section: Discussionmentioning
confidence: 99%